The Existence of Sheikh Burhanuddin's Tomb: A Study of the Religious System of the Community in Nagari Manggopoh Palak Gadang, Ulakan Tapakis District, Padang Pariaman Regency. - Annisa Tul Muharrara; Satie, Rustim (Kirana Publisher (KNPub), 2024)
Purpose of this study was to learn about the Syekh Burhanuddin tomb as a religious system in Nagari Maggopoh Palak Gadang and to understand the ritual processions at the tomb. The theory used in this study is of exsistensialism and religi. The findings of the Sheikh Burhanuddin tomb is how the tomb can still survive to this day as a reality in the intercession of the tomb. The tomb is qualitative research with an ethnographic approach. Data collection techniques include observation, interviews, library studies, and documentation. As for the findings of this study, the public believes that by pilgrimage to the grave, they can receive blessings and seek help through the medium of the the meditation has become something that society has decided upon. In addition to visiting the Syekh Burhanuddin tomb, it believed would bring blessings from the Syekh Burhanuddin. This culture is made into reality in the midst of society and it being something the cult.